Teologi Sosial dan Isu Lingkungan: Membangun Kesadaran Ekologis Berbasis Spiritual - Nadia Claudia Thomson (Berkat : Jurnal Pendidikan Agama dan Katolik, 2025)
This research examines the role of social theology in building spiritually-based ecological awareness amid global environmental crisis. Through a qualitative approach with literature study and content analysis methods, this research explores how religious values can contribute to environmental conservation efforts. The results show that social theology has significant potential in transforming the paradigm from anthropocentrism to spiritual eco-centrism through reinterpretation of religious doctrines and development of environmentally conscious spiritual practices. This study identifies several practical implementation models such as eco-pesantren programs and integration of environmental education in religious curricula. Despite facing challenges such as resistance to new interpretations of religious texts, the research finds great opportunities in increasing global awareness and support from mainstream religious institutions. This research recommends developing environmental theology curricula, strengthening networks between religious communities and environmental movements, and increasing research on religion-based ecological practices.